2015
DOI: 10.1007/s12010-015-1620-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Recombinant Zea mays Phenylalanine Ammonia-Lyase (ZmPAL2) and Its Application in trans-Cinnamic Acid Production from l-Phenylalanine

Abstract: Phenylalanine ammonia-lyase (PAL) is one of the most extensively studied enzymes with its crucial role in secondary phenylpropanoid metabolism of plants. Recently, its demand has been increased for aromatic chemical production, but its applications in trans-cinnamic acid production were not much explored. In the present study, a putative PAL gene from Zea mays designated as ZmPAL2 was expressed and characterized in Escherichia coli BL21 (DE3). The recombinant ZmPAL2 exhibited a high PAL activity (7.14 U/mg) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Phenylalanine is the precursor in the complex phenylpropanoid pathway ( Mitchell and Walters, 1995 ; Kato et al, 2000 ; Zang et al, 2015 ). In the present study, PAL, together with CAD and POD genes, were collectively up-regulated at the early stage of Ganoderma infection (1, 2, and 3 wpi).…”
Section: Discussionmentioning
confidence: 99%
“…Phenylalanine is the precursor in the complex phenylpropanoid pathway ( Mitchell and Walters, 1995 ; Kato et al, 2000 ; Zang et al, 2015 ). In the present study, PAL, together with CAD and POD genes, were collectively up-regulated at the early stage of Ganoderma infection (1, 2, and 3 wpi).…”
Section: Discussionmentioning
confidence: 99%
“…Only two maize PAL genes (originally named ZmPAL1 and ZmPAL2 ) have been cloned. Both were confirmed to encode proteins with PAL and tyrosine ammonia‐lyase (TAL) activities that effectively catalysed conversion of l ‐phenylalanine to trans ‐cinnamic acid (Rosler et al ., ; Zang et al ., ). It was shown that the expression of four ZmPAL genes (originally named ZmPAL1 , ZmPAL2 , ZmPAL4 and ZmPAL5 ) was strongly induced after nematode infection, while two others ( ZmPAL3 and ZmPAL6 ) were unresponsive (Starr et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Our previous research showed that the recombinant PAL from Zea mays (ZmPAL) was completely soluble and exhibited a satisfactory PAL activity (1.78 U mg −1 crude enzyme) in E. coli . In this study, a bioconversion process of l ‐phe to t ‐CA by using engineered whole‐cell E. coli expressing ZmPAL as the biocatalyst was investigated, and the conditions for t ‐CA production were optimized.…”
Section: Resultsmentioning
confidence: 99%
“…The reported ZmPAL2 lost c . 40% of its activity when 1.40 mmol L –1 t ‐CA was added to the reaction system . Hence, it could be concluded that the existence of t ‐CA would inhibit enzyme activity and decrease the efficiency of t ‐CA production.…”
Section: Discussionmentioning
confidence: 98%